Feasibility and Preliminary Effects of a Structured Walking Intervention on Body Composition Among Biomedical Science Students: A Pilot Study - Amelia, Poppy Fransisca; Prayogo, Fitra Adi (Universitas Karya Husada Semarang, 2026)
Background: Sedentary behavior among university students contributes to adverse changes in body composition and long-term metabolic risk. Walking represents a simple and accessible form of aerobic activity with potential health benefits. Objective: This pilot study aimed to evaluate the feasibility and explore preliminary trends in body composition changes following a four-week structured walking intervention among biomedical science students. Methods: A pilot quasi-experimental study with a one-group pretest–posttest design was conducted among three undergraduate biomedical science students. Participants performed 30 minutes of light-to-moderate intensity walking, 3–4 times per week, for four weeks. Body composition parameters—including body weight, body mass index (BMI), body fat percentage, muscle percentage, and visceral fat—were assessed using bioelectrical impedance analysis (BIA). Data were analyzed descriptively. Results: After four weeks, varied changes in body composition were observed across participants. One participant showed a tendency toward reduced fat percentage in the later weeks of intervention, while muscle percentage was generally maintained or slightly decreased. Body weight showed modest increases across all participants. No adverse events were reported, and all participants completed the protocol, indicating good feasibility. Conclusion: A structured walking program appeared feasible and was associated with preliminary trends in body composition among young adults, though the direction and magnitude of changes varied individually. The findings should be interpreted cautiously, given the very small sample size. Larger randomized controlled trials with longer follow-up and dietary monitoring are required to confirm these preliminary observations.